Analisis Kemampuan Membaca Pemahaman Kelas V SD - Amylia Putri; Hardina Eka Putri; Chandra Chandra; Ari Suriani (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
A person's reading comprehension ability is obtained from the learning process and perseverance. This research was conducted because of the need for a more in-depth analysis of students' reading comprehension abilities when learning Indonesian. This research aims to: 1) Analyze students' reading comprehension abilities; (2) Barriers faced by students in reading comprehension. This research is qualitative research using the case study method. Data collection techniques include observation, reading comprehension tests, and interviews. Analysis techniques include reduction, data presentation, and validation. The results of the research show that: (1) The reading comprehension abilities of fifth grade elementary school students are different. (2) Some of the obstacles faced by students include limited vocabulary, difficulty in understanding the context or background of the text, difficulty in connecting new information with existing knowledge and difficulty in analyzing information and deducing the meaning of the text. (3) There are two factors that cause difficulties in reading comprehension, namely internal factors (within the student) namely interest in reading and external factors (outside the student) namely the family environment and the school environment..